Testing the presence of implicit hiring quotas with application to German universities - Lena Janys (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Women are underrepresented in academia in general and economics in particular. I introduce a test to detect an under-researched form of hiring bias: implicit quotas. I derive a test under the null hypothesis of gender-blind hiring that requires no additional information about individual hires and can be used to analyze hiring bias in a variety of other hiring settings. I derive its asymptotic distribution and propose a parametric bootstrap procedure that resamples from the exact distribution. I analyze the distribution of female professors at German universities and find an implicit quota of one or two women on the department level.
Keywords: J71; C12; C18; 330; Gender; Academia; Bernoulli Sequences; Hypothesis Testing